แนวคิดการพัฒนายุทธศาสตร์การพัฒนาที่ยั่งยืน สำหรับมหาวิทยาลัยสงขลานครินทร์ - ทิพย์รัตน์ เทอดธิดา; เยาว์แสง ชยุตย์; วัฒนนิยมขจร อริยา (Trends of Humanities and Social Sciences Research, 2013)
ด้วยมหาวิทยาลัยสงขลานครินทร์ได้นำระบบบริหารคุณภาพตามนโยบายการกำกับดูแลองค์การที่ดีหรือ Organizational Governance (OG) มาใช้ประกอบการดำเนินงานเพื่อให้เกิดความมั่นใจแก่นักศึกษา ผู้รับบริการ ผู้มีส่วนได้ส่วนเสีย และบุคลากร ว่าการดำเนินงานของมหาวิทยาลัยเป็นไปอย่างเหมาะสม ซึ่งเป็นแนวการพัฒนามหาวิทยาลัยที่สอดคล้องกับแนวคิดการพัฒนาที่ยั่งยืน หน่วยตรวจสอบภายในแห่งมหาวิทยาลัยสงขลานครินทร์จึงได้ทำการวิเคราะห์ยุทธศาสตร์ของในการบริหารมหาวิทยาลัยและผลการดำเนินงานที่ผ่านมาเพื่อนำมากำหนดปัจจัยหลักของการพัฒนาที่ยั่งยืนสำหรับมหาวิทยาลัยสงขลานครินท์เพื่อเป็นข้อมูลให้ผู้บริหารทบทวนนโยบายการกำกับดูแลองค์การที่ดีและกำหนดมาตรการขับเคลื่อนนโยบายนี้ด้วยการวิเคราะห์สารสนเทศจริงตามค่านิยมหลักของการบริหารจัดการที่เป็นเลิศ Sustainable Development Concept for Prince of Songkla University Thoedtida Thipparat1, Chayut Yaowsaeng2 and Ariya Watniyomkajorn2 1Internal Audit Advisor, Internal Audit, Prince of Songkla University Hatyai, Songkhla 2Auditor, Internal Audit, Prince of Songkla University Hatyai, Songkhla Prince of Songkla University (PSU) uses a Quality Management System (QMS) based on organizational governance (OG) policy to ensure that the university will provide suitable services to students, customers, stakeholders and workforce. The QMS is a basic premise in creating the education for sustainable development (ESD). Internal Audit Prince of Songkla University has to explore key factors to set up ESD for PSU. Data associated with the management performance which was the result from the implementation of the university management strategies were determined in order to identify the key sustainable development factors. University administrators can use the identified factors to revise the organization policy and create the sustainable measures that can drive the policy by applying the fact based on analysis which is one of the core values of an excellent management model.